Challenges, Acceptance, and Adoption of Electronic Payment at Teodoro Arcenas Trade Center Towards Efficient Local Development - Glenn Mark A. Togle (International Journal of Law, Social Science, and Humanities, 2026)
The adoption of electronic payment systems is increasingly essential for enhancing business efficiency, customer satisfaction, and market competitiveness in local trade centers. This investigated the acceptability, challenges, and adoption of electronic payment systems among local suppliers, buyers, and vendors at the Teodoro Arcenas Trade Center in Roxas City. An explanatory-sequential mixed methods approach was utilized, guided by the Unified Theory of Acceptance and Use of Technology, involving 560 respondents and 10 participants for qualitative interviews. Results revealed that challenges in using electronic payments were generally low to moderate, with issues such as limited payment terminals and internet connectivity being the most notable. Acceptance and adoption levels were high, with respondents recognizing the systems’ security, ease of use, and usefulness. A significant relationship was found between acceptance and adoption, indicating that positive perceptions directly drive usage. Occupation significantly predicted acceptance, with vendors prioritizing operational efficiency, buyers valuing convenience, and suppliers emphasizing reliability and policy support. The study highlights the importance of improving digital infrastructure, expanding payment facilities, providing targeted training, and implementing occupation-specific policies to sustain adoption. These findings offer actionable insights for market administrators, policymakers, and payment providers to foster cashless transactions and support inclusive and efficient local economic development.